A Household Survey on Awareness of Hiv/Aids Among Rural People of Chandbela Vdc Of Eastern Nepal - Vijay Kumar Khanal; Bijay Thapa; Rajan Bikram Rayamajhi; Puspanjali Adhikari; Shyam Sundar Budhathoki; Anup Ghimire; Suman Bahadur Singh; Paras Kumar Pokharel (Journal of Nobel Medical College, 2015)
Background: In the past 20 years HIV/AIDS has become an increasing global phenomenon. The rising trend of morbidity and mortality has not only changed the demography but also poses a huge socio-economic burden on well-being of households, communities and country. In Nepal as the epidemic is maturing. However, the epidemic has never been maintained in the general population through heterosexual transmission in Nepal, rather it is driven by the infections among higher risk populations and their sexual partners.